Gdzie jest nasz dom? Historia pewnego filmu - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2017)
The article tells the story of the making of a little-known Polish documentary shot in 1944 and 1945. The film depicts the fate of a group of children from Warsaw who were at a summer camp in Stoczek Lukowski when the Warsaw Uprising began.